Exploring Hybrid Contracts Through Sharia Innovation on Digital Fintech Platforms - Masitah, Dian; Wahyudi, Amin (Jurnal Iqtisaduna, 2025)
The development of Islamic finance has driven the emergence of more complex contractual innovations, including hybrid contracts (multi-contract structures) that combine two or more contracts within a single transaction. This study aims to examine the position and challenges of hybrid contracts within the context of Islamic banking and fintech, particularly following the enactment of Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK), which does not yet provide detailed regulations on such mechanisms. Using a qualitative method, the study analyzes literature in fiqh muamalah, DSN-MUI fatwas, regulations from OJK and Bank Indonesia, and academic journals through thematic classification and source triangulation. The findings indicate that many Islamic scholars permit hybrid contracts, provided they are free from riba (usury), gharar (excessive uncertainty), and maysir (gambling). Key challenges include regulatory fragmentation and the underdeveloped dispute resolution mechanisms. A more comprehensive framework for derivatives and Sharia supervision is urgently needed to support modern Islamic finance practices.